Distribution and Development of the Wasp, Microgaster manilae (Ashmead) [Hymenoptera: Braconidael, in the Cutworm, Spodoptera litura(F.) - Herminigildo Torreno (Davao Research Journal)
Laboratory tests and field observation/collection were done in Ilocos Norte in 1990-91 to determine the developmental periods and occurrence of the parasitic wasp, Microgaster manilae (Ashmead). The latter was also determined in Northern Samar (1994) and Davao Oriental (1996) to have an insight of the Braconid's distribution. The parasitoid had a higher success of development in, and/or preference for the second instar cutworm larva. Its egglarval development ranged from 7 to 13 days with a mean of 8 and 13 days in the first and second instars, respectively. Pupal period was completed in days with the adult emerging usually in the morning. The occurrence of the Braconid in the north, central and southern part of the Philippines suggests its relatively wide distribution.